2019
DOI: 10.1096/fj.201802040r
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A decreases the anabolic bone response to mechanical loading by suppressing bone formation

Abstract: Increased vitamin A consumption is associated with decreased cortical bone mass and increased fracture risk in humans. Rodent studies have demonstrated that hypervitaminosis A increases cortical bone resorption, whereas the importance of the effects on bone formation is less well defined. We used an experimental model of increased bone formation by loading of the tibiae to investigate the effect of vitamin A on bone formation. Control [retinol activity equivalents (RAE) 4.5 µg/g chow] or vitamin A (RAE 60 µg/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…For control animals not subjected to tibial loading, retinyl acetate supplementation induced no changes in trabecular bone microstructure and osteogenic gene expression. However, retinyl acetate supplementation promoted BFR, mineralising surface (MS) and MAR at endocortical region but decreased Ct.Ar, Ma.Ar, Ec.Pm, and Ps.Pm [ 18 ]. In another study involving mature female Sprague Dawley rats, retinyl palmitate (natural alternative of retinyl acetate) and retinyl acetate were enriched in the diet (120 or 600 IU/g pellet) and given to the animals for 12 weeks.…”
Section: Effects Of Vitamin a On Bone Health In Animalsmentioning
confidence: 99%
“…For control animals not subjected to tibial loading, retinyl acetate supplementation induced no changes in trabecular bone microstructure and osteogenic gene expression. However, retinyl acetate supplementation promoted BFR, mineralising surface (MS) and MAR at endocortical region but decreased Ct.Ar, Ma.Ar, Ec.Pm, and Ps.Pm [ 18 ]. In another study involving mature female Sprague Dawley rats, retinyl palmitate (natural alternative of retinyl acetate) and retinyl acetate were enriched in the diet (120 or 600 IU/g pellet) and given to the animals for 12 weeks.…”
Section: Effects Of Vitamin a On Bone Health In Animalsmentioning
confidence: 99%
“…Previous studies in vivo and in vitro have indicated that a high concentration of preformed VA negatively affects both osteoblast differentiation and mineralization, owing to the effects of VA on osteogenic gene inhibition, osteoclastogenic gene activation, and osteocyte or osteoblast-related peptides modulation [ 9 ]. Through an animal experiment using female C57BL6/J mouse models, researchers reported a significant increase in the osteoclast number and the osteoclastogenic gene expression in mice that were treated with high doses of dietary retinyl acetate [ 35 ]. Moreover, VA antagonizes vitamin D (VD) by increasing calcium absorption and maintaining a steady-state serum calcium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that vitamin A-induced resorption initially occurs in the periosteal bone, and subsequently in the endosteal bone [ 12 ]. In addition to decreased periosteal bone thickness, retinol has also been shown to reduce mechanical loading-induced bone formation in mice after 6-weeks of treatment, largely through decreasing the bone formation rate (BFR) of osteoblasts [ 22 ]. In future studies, it will be important to extend the treatment period to determine whether the osteoclasts would be detectable in response to COD treatment.…”
Section: Discussionmentioning
confidence: 99%